Understanding and treatment of brake pipe fracture of metro vehicle bogie. (October 2021) - Xie, Chenxi; Tao, Gongquan; Liang, Shulin; Wen, Zefeng
Highlights: The causes of a brake pipe fracture on a metro train are revealed through a series of systemic field experiments. A dynamic stress analysis method that considers the frequency and time domains is presented to assess the possible measures to solve the pipe fracture problem. The main cause of a brake pipe fracture is the coupling resonance between the brake pipe and the bogie frame. The wheel out-of-roundness is the main excitation source. After adding a pipe clamp on the middle of the brake pipe and applying a regular wheel re-profiling, no brake pipe fracture occurred on the investigated metro line. Abstract: In a railway vehicle air brake system, a brake pipe is used to connect all related elements, for example, the air source system, brake control device, and brake valve. The brake pipe has a significant impact on the safety and reliability of trains. This paper presents a fracture analysis of a brake pipe installed on the bogie of a metro train running on one metro line in China. The analysis was conducted using a brake pipe modal test in a depot, a bogie vibration test, and a brake pipe dynamic stress measurement applied at the field site. The field experiment results indicate that the main cause of a brake pipe fracture is the coupling resonance between the first-order lateral bending eigenmode of the brake pipe (74 Hz) and the eigenmode of the reverse yawing of two side beams of the bogie frame (73 Hz). The wheel out-of-roundness is the main excitation source. To solve the pipe fracture problem, a dynamic stress analysis method that considers the frequency and time domains is presented to assess the possible measures. The measures investigated in this study are the pipe wall thickness, pipe clamp stiffness (elastic modulus), and pipe clamp numbers. The simulation results and on-track tests show that doubling the pipe wall thickness and decreasing the elastic modulus of the pipe clamp by 5.67 fold can reduce the dynamic stress amplitude of the pipe by approximately 60%. If a pipe clamp is added at the middle position between the two pipe clamps on the pipe, the dynamic stress amplitude of the pipe will decrease by 94% compared to the present pipe structure. This is because the additional pipe clamp alters the frequency of the first-order lateral bending eigenmode of the brake pipe to avoid being equal to the eigenfrequency of the reverse yawing of the two side beams of the bogie frame. After the metro corporation added a pipe clamp and applied a regular wheel re-profiling, no brake pipe fracture occurred on the investigated metro line.